Geschichte Syriens im 2. und 1. jahrtausend v.chr.: forschungsstand, probleme und perspektiven - Klengel, H. (ISIMU, 2016)
Syrian history began to develop as an own field of Ancient Near Eastern studies about fifty years ago when new textual and archaeological evidence was discovered and published. Dnring the last decade of years not only the 3rd milienninm (Ebla etc.), but also the 2nd and 1st miliennia were object of historical studies, devoted to the varions regions of Syria and to the system of rule exercised temporarily by foreign powers. Special attention found the period of Yamkhad. the kingdoms of Ugarit and Amurru, the "crisis years" at the end of the 2nd miliennium and the extension of Assyrian power during the early 1st miliennium. The contribution will follow the course of history and concentrate on results and open questions, also pointing to perspectives of research.